2006
DOI: 10.1007/s10096-006-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with urinary tract infection in diabetic patients with and without asymptomatic bacteriuria

Abstract: In order to compare the incidence of symptomatic urinary tract infection (UTI) in diabetic patients with and without asymptomatic bacteriuria (ASB), and to identify other risk factors for these infections, 289 females and 168 males were studied over a 12-month period. Symptomatic UTI occurred in 69.2% of patients with ASB (67.6% female and 76.5% male) versus 9.8% without ASB (14.9% female and 2.6% male). ASB and urinary incontinence were associated with symptomatic UTI in both women and men. Other risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 15 publications
8
35
0
2
Order By: Relevance
“…These findings are in agreement with those in previous reports suggesting an association between elevated HbA1c levels and the presence of UTIs 19,20. Ribera et al found that a HbA1c level >7% was associated with symptomatic UTIs in patients with DM,15 but this variable did not remain a risk factor when logistic regression analysis was applied. Other reports also have not found a correlation between metabolic control and the presence of UTIs 5,12,1618,21…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in agreement with those in previous reports suggesting an association between elevated HbA1c levels and the presence of UTIs 19,20. Ribera et al found that a HbA1c level >7% was associated with symptomatic UTIs in patients with DM,15 but this variable did not remain a risk factor when logistic regression analysis was applied. Other reports also have not found a correlation between metabolic control and the presence of UTIs 5,12,1618,21…”
Section: Discussionsupporting
confidence: 92%
“…The presence of ASB is a major risk factor for developing symptomatic UTIs,15 the present study identifying ASB as the most prevalent type of UTI in patients with DM (9%), with a prevalence similar to that reported in other previous studies. A meta-analysis of 22 studies regarding ASB in patients with DM has shown a prevalence of ASB of 12.2%, higher in females (14.2%) than in males (2.3%),16 similar to the present study’s findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…3 The incidence of diabetes mellitus (DM) throughout the world is increasing strikingly and is becoming a serious public health problem especially in the developing countries. 4 Diabetes mellitus is associated with many complications and in the long run it has some major effects on the genitourinary system which makes diabetic patients more liable to UTI and particularly to upper urinary tract infections. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Prospective, observational studies performed in Spain and Australia [5,6] indicated that ASB is the major risk factor for the development of complications, such as symptomatic UTI (including sepsis), in diabetic patients. However, a placebo-controlled, double blind, prospective clinical trial [7] performed in the United States that involved diabetic women failed to conclude that treatment of ASB reduces such complications.…”
mentioning
confidence: 99%